Mechanism of Rh prophylaxis: an experimental study on specificity of immunosuppression. Issue 5962 (12th April 1975) - Woodrow, J C; Clarke, C A; Donohow, W T; Finn, R; McConnell, R B; Sheppard, P M; Lehane, D; Roberts, F M; Gimlette, T M
Abstract : The mechanism by which Rh immunization is prevented by IgG anti-D was investigated by studying the specificity of immunosuppression. 62 D-negative Kell(K)-negative male volunteers were given two successive stimuli of 1 ml D-positive K-positive red cells. Thirty-one of the volunteers were also given 13-14 mug of IgG anti-K immediately after each stimulus, the others acting as controls. Anti-D developed in 11 of the 31 controls and in one of the 31 volunteers who had received anti-K. This marked suppression of the anti-D response by IgG anti-K was accompanied by the rapid clearance of the injected red cells to the spleen. This shows that the predominant mechanism that must be operating when IgG anti-D prevents Rh immunization is not antigen specific but is one that must involve the whole red cell, probably through destruction within splenic macrophages.